Practical guide for pediatric pulmonologists on imaging management of pediatric patients with COVID‐19. Issue 9 (1st July 2020) - Foust, Alexandra M.; McAdam, Alexander J.; Chu, Winnie C.; Garcia‐Peña, Pilar; Phillips, Grace S.; Plut, Domen; Lee, Edward Y.
Abstract: Understanding of coronavirus disease 2019 is rapidly evolving with new articles on the subject daily. This flood of articles can be overwhelming for busy practicing clinicians looking for key pieces of information that can be applied in daily practice. This review article synthesizes the reported imaging findings in pediatric Coronavirus disease 2019 (COVID‐19) across the literature, offers imaging differential diagnostic considerations and useful radiographic features to help differentiate these entities from COVID‐19, and provides recommendations for requesting imaging studies to evaluate suspected cases of pediatric COVID‐19.